Genomics of Aminoglycoside Resistance in Pseudomonas aeruginosa Bloodstream Infections at a United States Academic Hospital - Giancarlo Atassi; Rachel Medernach; Marc Scheetz; Sophia Nozick; Nathaniel J. Rhodes; Megan Murphy-Belcaster; Katherine R. Murphy; Arghavan Alisoltani; Egon A. Ozer; Alan R. Hauser (Microbiology Spectrum, 2023)
ABSTRACT Pseudomonas aeruginosa frequently becomes resistant to aminoglycosides by the acquisition of aminoglycoside modifying enzyme (AME) genes and the occurrence of mutations in the mexZ, fusA1, parRS, and armZ genes. We examined resistance to aminoglycosides in a collection of 227 P. aeruginosa bloodstream isolates collected over 2 decades from a single United States academic medical institution. Resistance rates of tobramycin and amikacin were relatively stable over this time, while the resistance rates of gentamicin were somewhat more variable. For comparison, we examined resistance rates to piperacillin-tazobactam, cefepime, meropenem, ciprofloxacin, and colistin. Resistance rates to the first four antibiotics were also stable, although uniformly higher for ciprofloxacin. Colistin resistance rates were initially quite low, rose substantially, and then began to decrease at the end of the study. Clinically relevant AME genes were identified in 14% of isolates, and mutations predicted to cause resistance were relatively common in the mexZ and armZ genes. In a regression analysis, resistance to gentamicin was associated with the presence of at least one gentamicin-active AME gene and significant mutations in mexZ, parS, and fusA1. Resistance to tobramycin was associated with the presence of at least one tobramycin-active AME gene. An extensively drug-resistant strain, PS1871, was examined further and found to contain five AME genes, most of which were within clusters of antibiotic resistance genes embedded in transposable elements. These findings demonstrate the relative contributions of aminoglycoside resistance determinants to P. aeruginosa susceptibilities at a United States medical center. IMPORTANCE Pseudomonas aeruginosa is frequently resistant to multiple antibiotics, including aminoglycosides. The rates of resistance to aminoglycosides in bloodstream isolates collected over 2 decades at a United States hospital remained constant, suggesting that antibiotic stewardship programs may be effective in countering an increase in resistance. Mutations in the mexZ, fusA1, parR, pasS, and armZ genes were more common than acquisition of genes encoding aminoglycoside modifying enzymes. The whole-genome sequence of an extensively drug resistant isolate indicates that resistance mechanisms can accumulate in a single strain. Together, these results suggest that aminoglycoside resistance in P. aeruginosa remains problematic and confirm known resistance mechanisms that can be targeted for the development of novel therapeutics.